Implementation of Vocational Skills Program for Intellectual Disabilities: Evaluation Study with CIPP (Context, Input, Process, Product) - Rizky Amalia Rosyidi; Ahsan Romadlon Junaidi; Asep Sunandar (Journal of ICSAR, 2022)
This study aims to determine the implementation of vocational skills programs for mental disabilities in terms of context, input, process , and product . At the same time knowing the supporting and inhibiting factors for implementing vocational skills programs for mental disabilities in special schools. The design used is a holistic single-case study. The analysis technique used is Miles and Huberman's data analysis technique which consists of data reduction, presenting data and drawing conclusions/verification. Checking the validity of the data is done through triangulation of data/sources and triangulation of methods. The results of this study are in the form of an overview of the implementation of the vocational skills program for mental disabilities at Pembina SLB Malang in terms of context, input, process, and product aspects. As well as the supporting and inhibiting factors for its implementation.